The impact of SO2 emissions trading scheme on pollution abatement and labor market for industrial enterprises in China - Zhang, Weijie; Zhang, Panpan; Niu, Xiaodi (Frontiers in Environmental Science, 2024)
To cope with the emissions permit trading program, industrial firms have to change production decisions, which may affect their pollution discharge, labor demand, and workers’ wage earnings. Using a time-varying difference-in-differences framework together with robustness checks, this research explores the impacts of the SO2 emissions trading scheme (SETS) on SO2 emissions, employment, and wages of industrial firms in China. It was noted that the program resulted in a remarkable decline not only in SO2 emissions but also in labor demands and wages. The mechanism analyses further show that emissions reduction is mainly driven by fossil energy input decrease rather than by desulfurization technology. The negative effects of employment and wages are driven by the negative output effect and insufficient technology rather than by the environmental substitute effect. Our findings contribute to the improvement of the market-oriented environmental permit trading program and development of regulated firms in developing countries.